Consider the generalization of the Fibonacci sequence: define the -bonacci sequence such that its term is sum of the previous terms with initial terms: .
Now we denote the term of the -bonacci sequence as . Calculate the limit below.
Details and Assumptions :
As an explicit example: if , we will get a Fibonacci sequence, which means the limit is .
You do not need computational aids to solve this problem.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let lim m → ∞ W m , n W m + 1 , n = R . It is easily shown that R n = R n − 1 + R n − 2 + R n − 3 + … + 1 . Using the formula for a geometric series, this simplifies to R n = R − 1 R n − 1 . Rearranging, we get R n + 1 − 2 R n + 1 = 0 . Dividing by R n , R − 2 + R n 1 = 0 . Taking the limit as n → ∞ , R − 2 = 0 , or R = 2 .